Given "(2y^3-x^3)dx+3x^2ydy=0"
"\\frac{dy}{dx} = -\\frac{(2y^3-x^3)}{3x^2y} = \\frac{(x^3-2y^3)}{3x^2y}"
Let y = vx, then "\\frac{dy}{dx } = v+x\\frac{dv}{dx}"
"v+x\\frac{dv}{dx} = \\frac{(x^3-2v^3x^3)}{3x^3v} = \\frac{1-2v^3}{3v}"
"x\\frac{dv}{dx} = \\frac{1-2v^3}{3v}-v = \\frac{1-2v^3-3v^2}{3v}"
"\\frac{3vdv}{1-2v^3-3v^2} = \\frac{dx}{x}"
Integrating both sides,
"\\int \\frac{3vdv}{1-2v^3-3v^2} =\\int \\frac{dx}{x}"
Doing partial fractions,
"\\frac{3v}{1-2v^3-3v^2} = \\frac{1}{9(v+1)} -\\frac{1}{3(v+1)^2}-\\frac{2}{9(2v-1)}"
Now integrate both sides,
"\\int \\frac{1}{9(v+1)} -\\frac{1}{3(v+1)^2}-\\frac{2}{9(2v-1)} dv =\\int\\frac{dx}{x}"
"\\frac{1}{3}ln|v+1| +\\frac{1}{v+1} -\\frac{1}{3}ln|2v-1| = ln|x| + ln|C|"
"\\frac{1}{3}ln|\\frac{v+1}{2v-1}| +\\frac{1}{v+1} = ln|Cx|"
Simply putting "v = \\frac{y}{x}"
"\\frac{1}{3}ln|\\frac{y+x}{2y-x}| +\\frac{x}{y+x} = ln|Cx|"
Comments
Leave a comment